An Urban Colour Space in the Context of Culture - Zheleznyak, Olga (project baikal, 2015)
A colour space is seen as an actual discourse when discussing problems of formation and inhabitation of the modern city environment. The key aspect of such understanding is an activity-cultural interpretation of the urban environment colouristics proposed by the author, which allows building of an integral sphere of colour existence. This model of working with colour includes basic components and structures a colour space, while matching up all the elements (basic paradigms that provide proper functioning and development of the colour space; mechanisms of formation of colour paradigms; processes of formation and transformation of cultural norms and stereotypes; the culture of colour as a holistic unit that penetrates the variety of colour space forms, as well as the reality of colour establishment in the framework of human culture; the urban colouristics as a material and virtual, artificial and natural, organized and spontaneously appearing colour reality together with professional and conventional visions of it, etc.).
Keywords: colour space; urban environment; ambivalence of colour; colour culture; colour norms and canons; mastering; colour and light transformations; worldviews; urban colouristics